KONSTRUKSI MAKNA MEDIA SOSIAL ASK.FM BAGI PENGGUNA DI KOTA PEKANBARU - Putri Elza; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The development of technology in communication raises the growth of social networking sites that Ask.fm now becomes a popular social network that is loved by many people everywhere, especially in Pekanbaru. The use of social networking Ask.fm as a virtual communication media raises various meanings associated with the reasons why they choose to use the Ask.fm as a social network they use. This study aims to determine the motive, meaning features Ask.fm, and the meaning of friendship on the user experiences among other users in communication in virtual life.This research is a qualitative research with phenomenological approach. The Informants in this study were 5active Ask.fm users from various backgrounds who live in Pekanbaru, selected using purposive technique. The data was collected through observation, interviews, and documentation. The data analysis technique includes data reduction, data presentation and conclusion and verification.The results indicates that the motive for using the Ask.fm as a virtual communication media among the informants consists of a Becauseto motive namely are trend, follow and unique, while in order to motive are the curiosity and the information provided in Ask.fm. Making meaning of features Path as media of communications among the informants consists of Ask.fm as media for the exchange of information, Ask.fm as a means to express feelings, Ask.fm as entertainment media and Ask.fm as a means for chatting. Meaning of friendship in Ask.fm as a virtual communication media among the informants that experience a positive relationship to expand friendship networking and to build a good friendship, while the negative friendship experiences such termination of friendships may occur as a result of the perceived discomfort and the chance of cyber bullying that often occurs in social media.Keywords: Social media, Ask.fm, Construction of Meaning